Impact of auditory deprivation on tennis performance and perceived exertion - Kolar, J.; Kolar, P.; Modrak, M.; Veselý, V.; Kobesova, A. (International Journal of Sports Physiology and Performance, 2025)
Purpose: This study aimed to evaluate the impact of auditory deprivation on tennis-stroke accuracy and perceived exertion among tennis players, with a focus on understanding how auditory inputs affect sport performance.